Analisis Kebijakan Musyawarah Perencanaan Pembangunan (MUSRENBANG) Kabupaten Sumenep - Moh. Farid; Totok Sasongko; Annisa Purwatiningsih (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2020)
The Process of Development Planning Discussion (MUSRENBANG) is successful if the result of Muernbang can be implemented become maximal. So in the Implementation of both from the village level, sub district level, regencg level even merely fulfill the obligations for the realization of the program, but can be implemented well from the result of MUSRENBANG. The type of this riset are use descriptive quantitative method, secandary data and primary data, in this case we use accumulate data thecniqve by specific interview observation and documentation. While, to choose the informan we use purposive sampling thecniqve and analysis data thecniqve by reduction of data, presenting data and then we dray the conclusion. From the result of this riset, the government of Sumenep regency that belongs in the unit of work on that region have been done the MUSRENBANG of both from the village level, become maximal. Even merely fulfill doing the process of MUSRENBANG wel done. Althaugh there are some unrealization program, but it can understandabhg, because the limitations of the budget provided by the government. But the appreciation of Jawa Timur governoor about Sumenep regency is being process and MUSRENBANG Implementation of Sumenep regency is trully kept and the government of Sumenep regency responsibly.